Unusual Cause of Panfacial Fracture in Paediatric Patient: A Case Report - Abdullah, Mohd Faizal; Fauzi, Fattirah Auni; Lim Min Jim; Md yusoff, Bazli (Journal of Liaquat University of Medical & Health Sciences, 2025)
Due to the rarity of pediatric panfacial trauma, there are unclear effects on the developing child. Treatment algorithms largely follow adult panfacial protocols. These include limited exposure to prevent disruption of osseous sutures and synchondroses' growth centres, enhanced healing and remodelling capacities that favour nonoperative management, and innovative fracture fixation techniques in the context of an immature craniomaxillofacial skeleton in the pediatric population. The resulting damage to soft tissue and bone structures is frequently so severe that it calls into question of the previously established guidelines for the treatment of pediatric facial fractures. Due to the unique characteristics of the developing facial skeleton, surgeons frequently face challenges when managing facial fractures in children. The goal of therapy for fractures in children should be as conservative as feasible, use the least intrusive surgical technique to access the fracture and the least invasive surgical fixation to allow for stable reduction and avoid any disruptions to growth. We report a case of a rare cause of panfacial fracture with split palate in an eight-year-old boy and its management.